PECULIARITIES OF PREPARATION FOR ENTREPRENEURSHIP OF FUTURE SPECIALISTS IN TRANSPORT MANAGEMENT AND LOGISTICS IN UKRAINE (Innovative professional education, 2024)
At the present stage, any interactions, both at the global and local levels, are formed in the context of fierce competition and constant crisis situations observed in Ukraine. These constant changes in the economic life of the country have led to the need to train specialists in the field of logistics. It is no longer enough to use only economic approaches to achieve significant results in business. Today, it is necessary to apply modern progressive methods of managing flow processes to effectively solve the challenges faced by businesses in the face of constant changes in the market and economic difficulties. In preparing for entrepreneurial activity in the field of logistics in Ukraine, it is important to take into account technological orientation, adaptation to market conditions, development of partnerships, knowledge of local legislation and continuous educational training. Only by taking these aspects into account can entrepreneurs successfully compete in the market and effectively implement modern methods of managing logistics processes. Peculiarities of preparation for entrepreneurship in the field of logistics in Ukraine are determined not only by technical aspects, but also by the specifics of the market and the country's economic  situation
Keywords: entrepreneurship, transport, logistics, vocational education, qualities of a successful entrepreneur, problems of preparation for entrepreneurship, professional competence